2021
DOI: 10.12911/22998993/132995
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Carvones from Various Essential Oils and Their Ability to Increase the Stability of Fat-Containing Products

Abstract: One of the crucial factors for the improvement of people's health is the rationalization of nutrition. The unbalanced food ration, along with some ecological problems becomes the reason for serious disorders in the functioning of a human body. The appearance of these disorders depends greatly on food quality, the contents of essential substances in it, safety as well as its chemical composition. Vegetable oils belong to the most widely used products of the everyday food ration.They comprise essential fat-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The optical isomers of carvone can impart certain flavours to foods, and when creating functional fatcontaining products, it is possible to use both optical forms of carvone, depending on the orientation of a new functional product. Research by Frolova et al (2021) on the method of accelerated oxidation has shown that the introduction of carvone in the form of optical isomers into sunflower oil leads to an increase in the concentration of fatty products by 2.4-3.0 times in the values of the peroxide number and 1.5-1.7 times in the values of the acid number in comparison with the control. Comparing the effect of the optical isomers of carvone on the oxidation dynamics of fatty products, it was found that in general their protective effect is similar.…”
Section: Carvone Is An Important Monoterpene Ketone Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical isomers of carvone can impart certain flavours to foods, and when creating functional fatcontaining products, it is possible to use both optical forms of carvone, depending on the orientation of a new functional product. Research by Frolova et al (2021) on the method of accelerated oxidation has shown that the introduction of carvone in the form of optical isomers into sunflower oil leads to an increase in the concentration of fatty products by 2.4-3.0 times in the values of the peroxide number and 1.5-1.7 times in the values of the acid number in comparison with the control. Comparing the effect of the optical isomers of carvone on the oxidation dynamics of fatty products, it was found that in general their protective effect is similar.…”
Section: Carvone Is An Important Monoterpene Ketone Componentmentioning
confidence: 99%
“…However, the left carvone shows a greater effect on the resistance of sunflower oil compared to the right carvone. In addition to protection against oxidation, the optical isomers of carvone may have a physiological effect on the human body (Frolova et al, 2021).…”
Section: Carvone Is An Important Monoterpene Ketone Componentmentioning
confidence: 99%
“…Natural products show great potential in the design and discovery of green herbicidal molecules because of their ecofriendliness, extensive source, chemical modifiableness, among others. [3][4][5][6] Carvone, a chiral ketone-bearing monocyclic monoterpene structure, is naturally found in various plant essential oils, 7 such as spearmint (Mentha spicata), 8,9 caraway (Carum carvi), 10 and dill (Anethum graveolens), 11 and it has been applied as a building block to construct some bioactive compounds. 12,13 Besides, according to the reported literature, [14][15][16] 1,2,4-triazole-thioether moiety could serve as a promising pharmacophore for the design, discovery, and development of new green herbicides.…”
Section: Introductionmentioning
confidence: 99%